NTRK rearranged sarcoma of the bone. Role for larotrectinib in the neoadjuvant setting of an ultra-rare tumor: a case report - Palmerini, Emanuela; Frega, Giorgio; Gambarotti, Marco; Frisoni, Tommaso; Cesari, Marilena; Bazzocchi, Alberto; Miceli, Marco; Donati, Davide Maria; Fanti, Stefano; Nanni, Cristina; Benini, Stefania; Longhi, Alessandra; et al. (Frontiers in Oncology, 2023)
Background: Neurotrophic tyrosine receptor kinase (NTRK) gene-fusion targeted molecules revolutionized the paradigm of treatment of a limited subgroup of cancers of various histologies. Entrectinib and larotrectinib obtained unprecednteded response rates in patients with cancer harboring NTRK rearrangements. This evidence recently led to the agnostic approval of these drugs and evidence (confirmation) of their activity in a broader disease setting is emerging.Here we report the case of a patient affected by EML4-NTRK3 rearranged undifferentiated spindle cell bone sarcoma treated with larotrectinib, and we argue (discuss about) the incidence and clinical presentation of NTRK gene-fusion positive bone sarcomas, the potential use of upfront treatment with NTRK-inhibitors in neoadjuvant setting and the role of multidisciplinary tumor board.Despite the rarity of these rearrangements in patients with primitive bone sarcomas, the therapy with NTRK inhibitors represents a highly effective strategy to be pursued in selected cases even in neoadjuvant setting. The management of these very rare cancers should always be discussed in a multidisciplinary board of reference centers.